CCCRIS programme of activities - 1997 to 2000 - Griffith, David M ([CCCRIS] [Georgetown]GY, 1996)
Examines some significant issues related to current developments in information technology, such as the internet, intranets, and New Interactive Communication Technology. Identifies projects and activities for the CCCRIS work programme 1997-2000.